Bombay Lectures on Highest Weight Representations of Infinite Dimensional Lie Algebras - Kac, Victor G.; Raina, Ashok K.; Rozhkovskaya, Natasha (Singapore: World Scientific Publishing, 2013)
The second edition of this book incorporates, as its first part, the largely unchanged text of the first edition, while its second part is the collection of lectures on vertex algebras, delivered by Professor Kac at the TIFR in January 2003. The basic idea of these lectures was to demonstrate how the key notions of the theory of vertex algebras--such as quantum fields, their normal ordered product and lambda-bracket, energy-momentum field and conformal weight, untwisted and twisted representations--simplify and clarify the constructions of the first edition of the book. --
Includes bibliographical references (pages 229-234) and index.
Keywords: Infinite dimensional Lie algebras; Quantum field theory; Mathematics